Early Thrombotic Microangiopathy After ABO-Incompatible Living Donor Kidney Transplantation - Dominique Bertrand; Arnaud Del Bello; Rebecca Sberro Soussan; Sophie Caillard; Guillaume Claisse; Lionel Couzi; Sophie Girerd; Alexandre Hertig; Yannick Le Meur; Vincent Pernin; Coralie Poulain; Cédric Rafat; et al. (Kidney International Reports)
Introduction: Although long-term graft survival is comparable with that of ABO-compatible (ABOc) renal transplantation, the risk of antibody-mediated rejection (ABMR) following ABO-incompatible (ABOi) transplantation is higher and can occur as an early thrombotic microangiopathy (TMA). Methods: We designed a retrospective multicenter study, including all patients who presented with a TMA (histological and/or biological) after an ABOi transplantation (< 1 month) and compared with matched controls who had a favorable initial course with a normal biopsy. Results: Between 2013 and 2022, 375 ABOi kidney transplants were performed and 23 patients (6.1%) developed TMA (median: 1 day, interquartile range [IQR]: 0–3 days). Twenty-one patients (91.3%) had biological TMA. Among 23 early graft biopsies, histological evidence of active TMA was found in 17 cases (80.9%). All patients received treatment: 20 of 23 received at least 1 session of plasmapheresis and 19 of 23 received at least 1 injection of eculizumab. Eight early graft losses (30.4%) occurred (median: 7 days, IQR: 3–16 days). IgG and IgM anti–blood group antibody (ABGA) levels (peak and last pregraft assay) were significantly higher in the TMA group (peak: P = 0.01 for IgG and P = 0.0006 for IgM; last assay before kidney transplantation [KT]: P < 0.0001 for IgG and P = 0.0003 for IgM). A level ≥ 1/8 for IgG and ≥ 1/4 or IgM before transplantation were significantly and independently predictive of the occurrence of TMA. No other predictive factors were found. Conclusion: TMA after ABOi transplantation is not a rare phenomenon and is associated with a poor prognosis in nonresponders-to-treatment patients. ABGA titer performed by hemagglutination is an imperfect marker of the occurrence of such a phenomenon.